Mycophenolate mofetil for the treatment of children with immune thrombocytopenia and Evans syndrome. A retrospective data review from the Italian association of paediatric haematology/oncology. (22nd July 2016) - Miano, Maurizio; Ramenghi, Ugo; Russo, Giovanna; Rubert, Laura; Barone, Angelica; Tucci, Fabio; Farruggia, Piero; Petrone, Angelamaria; Mondino, Anna; Lo Valvo, Laura; Crescenzio, Nicoletta; Bellia, Francesco; et al.
Summary: Mycophenolate mofetil (MMF) has been shown to be effective in children with immune thrombocytopenia (ITP) and Evans syndrome (ES), but data from larger series and details on the timing of the response are lacking. We evaluated 56 children treated with MMF for ITP ( n = 40) or ES ( n = 16), which was primary or secondary to autoimmune lymphoproliferative syndrome ‐related syndrome (ARS). Thirty‐five of the 54 evaluable patients (65%) achieved a partial (18%) or complete (46%) response after a median (range) of 20 (7–137) and 37 (7–192) d, respectively. ITP and ES patients responded in 58% and 81% of cases ( P = not significant, ns), with complete response in 32% and 81% ( P = 0·01), respectively. 60% and 73% of children with primary disease and ARS responded ( P = ns) with complete response in 34% and 68% of cases ( P = 0·01), respectively. Six of 35 (17%) children relapsed after a median of 283 d (range 189–1036). Limited toxicity was observed in four patients. The median durations of treatment and follow‐up were seven and 12·7 months, respectively. This is the largest reported cohort of patients treated with MMF for ITP/ES. The results show that MMF is effective and safe and provides a relatively quick response, suggesting that it has a potential role as an alternative to more aggressive and expensive second/further‐line treatments.